Academic performance and emotional intelligence levels - Rodas Cabanillas, José Luis (2015)
This study had as a main purpose to determine the functional relationship and the significate correlation between the academic performance and the emotional intelligence levels of each student from the Facultad de Ciencias Físicas y Matemáticas de la Universidad Nacional Pedro Ruiz Gallo, located in Lambayeque city-Peru; the target is to determine the relationship between the academic performance and the emotional intelligence levels; the specific targets are focused on contrasting hypothesis, identifying the functional relationship and determining the nexus between the academic performance and the emotional intelligence, which allows to recognize the most important aspects, which are the emotional intelligence and how this affects into the personal relationship, also into the academic performance of course. This research is based on an explicative and applicate type, using a non-experimental design. The instrument validation to recollect the data for the Emotional Intelligence was made in a SPSS program, using the Cronbach alpha, resulting an alpha of 0-699; which concludes with a high trustworthiness questionnaire focused on the 30 random students from the Facultad de Ciencias Fisicas y Matematicas de la Universidad Nacional Pedro Ruiz Gallo, located in Lambayeue city-Perú. The selection of the probabilistic sample, using a random systematic sampling, using the academic performance variable in the pilot test about the 30 students, obtaining average of the students’ academic performance of 10.4773 and an standard deviation of ± 2.475426871, finding a sampling error of ± 0.88582 points in the academic performance and also a sampling error of ± 0.5, which was obtained from a 89 stundents’ sample and a ± 0.80 error points related to the academic performance, which was obtained from a 36 student’s sample; finishing as a posivite sample the one related to the 36 students. The positive sample related to the 36 students was used in this research, applying a test related to the Emotional Intelligence over the students, selected systemically from the group. The results related to the academic performance was filed in the pedagogic concern office in the Facultad de Ciencias Fisicas y Matematicas related to the students in the positive sample, then to associate the academic performance and the emotional intelligence in each one of the students from the positive sample, after that to analyze and qualify the results, as well as the statistics and also the statistics graphics and tables show. The results, obtained after the applying Z statistic test to give signification to the parameters according to the lineal model, because that is its tendency; a value of Zk= - 4.53 was calculated for the β0 signification and for the critical points of ± 1.96, because the signification level is 0.05. This means that β0 is different of negative zero and β1 parameter with the signification level of 0.05 and a critical value of ± 1.96, it calculates the value of Zk= 12.086, which means that the emotional intelligence levels affects in a significantly and positive way the academic performance of each student previously named. Rejecting in this way the invalid hypothesis because of a bilateral test. The correlation Spearman was applied for the emotional intelligence variables and the academic performance, calculating the Spearman‘s rho = 0.926, which showed that it exists a high, significant and positive correlation between the academic performance and the emotional intelligence levels, as recommends the statistics rules through the research made into the 36 students. To end, it can affirm that the academic performance is based on the emotional intelligence levels. This study will contribute to make more important the intrapersonal and interpersonal intelligence, which affects the academic performance of each student from the Facultad de Ciencias Físicas y Matemáticas de la Universidad Nacional Pedro Ruiz Gallo.